Telisa Shallow Marine Sandstone as an Emerging Exploration Target in Palembang High, South Sumatra Basin - , R.M. I. Argakoesoemah ([Yogyakarta] : Departemnts of Geological Engineering Faculty of, 2009)
The main productive reservoirs in the Palembang High, South Sumatra Basin, are sandstones of the Talang Akar Formation and carbonates of the Baturaja Formation. The largest oil field in the region is the Kaji-Semoga Giant Oil Field discovered in 1996. To maintain the production rate, exploration efforts continue with new ideas and concepts. It is believed that one of the potential exploration candidates is the Telisa Sandstone reservoir. The Telisa Sandstone, which includes the sandstones in the lower part of the Telisa Formation, consists of very fine- to fine-grained sandstones with minor shales, deposited in a shallow marine shoreface setting during both sea level lowstand and transgression. The acoustic impedance contrast between the sandstones and the overlying and underlying Telisa shales is very small because of highly argillaceous content of the sandstone. Consequently, the sandstone reservoir prediction becomes very difficult. In addition, the geophysical data available comprise only 2-D seismic in various vintages and qualities. The most crucial objective in this exploration effort is to predict the sandstone distribution, its quality and fluid content. This is required to generate a drillable prospect, add a development well, a work-over, and enhance field reserves calculation. The test-line work results of the Extended Elastic Impedance (EEl) Inversion technique have been applied and the delineation of sandstone distribution, determination of sandstone quality, and fluid content potential have been defined. The objective of this paper is to share the Telisa Sandstone geological interpretation and the use of the EEl inversion in exploration of low acoustic impedance contrast of clastic reservoir in the Palembang High region, South Sumatra Basin. The hydrocarbon potential in this Telisa Sandstone play remains unknown, but the results are encouraging. Several successful tests have been conducted through the hydraulic fracturing efforts. Although most of the sandstones are relatively tight, the reservoir flows oil. The petroleum system of this Early Miocene play remains uncertain, but it is believed that the source rocks are mature shales of the Lemat and Talang Akar Formations in the Jemakur Graben and Tamiang Lows immediately to the north. It is possible that the oil has been migrating from the fetch areas through the sandstones of the Talang Akar Formation and porous limestones of the Baturaja Formation. In the Kaji-Semoga Field, the Telisa Sandstone onlaps onto the Baturaja Formation. Fault conduits could also be an important role in oil migration process as indicated in the Langkap Field. The top and updip lateral seals are the thick, basinscale Telisa shales.